Introduzione - Patricia Gaborik; Stéphanie Lanfranchi; Élise Varcin (Laboratoire Italien)
In the wake of the recent publications on the centrality of culture in the Fascist totalitarian project, this issue examines Mussolini’s relationship to the arts and vice versa more specifically, probing the aesthetic and political aspects of representations (in literature, the performing and figurative arts, and radio) of the “duce” – both in Italy and in their circulation abroad.